Development of SiCaTu Busy Book Learning Media Assisted by Canva to Improve Elementary School Students’ Early Reading and Writing Skills - Sahida Nur Arofah; Diki Rukmana (FKIP - Universitas Riau, 2026)
This research was motivated by problems in students’ beginning reading and writing skills at elementary school levels due to the lack of interactive learning environments and engaging learning media. This study aimed to develop, determine the feasibility, and examine the effectiveness of the Busy Book Si Cerdas Baca Tulis (SiCaTu) learning media in improving elementary school students’ beginning reading and writing skills. This research employed a Research and Development (R&D) method using the ADDIE model. The subjects consisted of four validation experts and twelve students from grades 1 to 5. Data were collected through interviews, expert validation questionnaires, and pretest-posttest instruments. The needs analysis indicated the necessity of more engaging learning media to support students’ beginning reading and writing skills. The results showed that the SiCaTu Busy Book was highly feasible, with an average validation score of 95%. The media was also effective, indicated by an N-Gain score of 0.401 (moderate category) and a Wilcoxon test significance value of 0.0005 (<0.05). Thus, the SiCaTu Busy Book can support the improvement of students’ beginning reading and writing skills through interactive and engaging activities.